The Methuen Drama guide to contemporary Irish playwrights - Middeke, Martin; Schnierer, Peter Paul (Plays and Playwrights, 2010)
The Methuen Drama Guide to Contemporary Irish Playwrights is an authoritative single-volume guide to the work of twenty-five Irish playwrights from the 1960s to the present, written by a team of twenty-five eminent scholars from Ireland, the United States, Britain and Germany contributing individual studies to the work of each playwright. Each of the twenty-five chapters provides: a biographical introduction to the playwright and their work; a survey and concise analysis of each of the writer's published plays; a discussion of their style, dramaturgical concerns and the critical reception; and